Seroprevalence of Hepatitis B Virus Surface Antigen (HBsAg) in Patients Visiting Teaching Hospital of Jumla, Nepal - Pun Magar, Bibek; Thapa, Niresh; Rana, Elisha; Joshi, Keshav Raj; Tiwari, Arjun Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Background: Hepatitis B Virus (HBV) infection is a foremost global health problem. In the context of Nepal, the prevalence of HBV infection is found to be low, 0.9% (1.1% in males and 0.5% in females), though a high prevalence of ≥8% is shown among the population in the mountainous region by several studies. The epidemiology of HBV infection in the population of Jumla is not well-known. This study aimed to find out the seroprevalence of HBV surface antigen (HBsAg) in patients visiting Karnali Academy of Health Sciences Teaching Hospital (KAHS-TH), Jumla, Nepal. Methods: The cross-sectional study was conducted in people visiting KAHS-TH, Jumla for testing HBsAg from 1st April 2018 to 31st March 2019. The samples collected were tested for HBsAg by using the Rapid HBsAg test kit. All positive cases were further tested by the Chemiluminescence (CLIA) method for HBsAg. The data entry was done in Microsoft Excel. After transferring the data into SPSS version 16, data analysis was done.Results: In this study, 1704 individuals were screened during the period. Overall 53 (3.11%) were HBsAg positive. Among the total of 506 males and 1198 females, 22 (4.34%) males and 31 (2.58%) females were positive for HBsAg. The highest prevalence (8.1%) was observed in the age group of 40– 45 years. But the prevalence rate is zero in 0-5 years age group and above 65 years of age. Conclusion: The HBV infection was higher in Jumla as compared to that of the overall prevalence of Nepal. Males were highly infected than females and the middle age group was at the high-risk of HBV infection.